Study on the Influence of Oil Replacement on Furfural Content in Transformer Oil and Insulation Aging Assessment. Issue 2 (March 2020) - Tang, Xiaofeng; Su, Zhengyuxi; Chen, Peng; He, Cui
Abstract: The service life of a transformer was determined by the aging state of solid insulation. When the aging state of the transformer insulation reaches a certain level, oil replacement or oil filter was performed to improve the insulation ability of the insulating oil. A series of treatments of insulating oil inevitably result in the loss of furfural in the oil. In order to study the effect of oil replacement on the furfural content in oil, oil-paper insulation samples with different aging degrees were prepared under laboratory conditions. Besides, oil replacement was carried out in different aging stages, and the times of oil replacement was divided into once and multiple. Furthermore, the furfural content in oil was compared before and after oil replacement, and the effect of oil replacement on the furfural content in transformer oil was analyzed. The results showed that oil replacement had little effect on furfural content in the early aging stage, while it has a greater effect on furfural content in the late aging stage. In addition, the cumulatively of multiple oil replacement on the loss of furfural in oil can cause greater deviations in transformer aging evaluation. Therefore, the effect of oil replacement on the evaluation of insulation aging of transformer is not negligible.